The simulation of coaches manual guidance techniques during the performance of a gymnastic skill - Jeraj, D.; Heinen, T. (Science of Gymnastics Journal, 2015)
The aim of this study was to explore the effect of different manual guidance techniques on performance-related variables of a backward salto. We simulated a backward salto by means of a computer model. Changes in performance-related variables were calculated as a result of isolated and combined hand applications. We created seven conditions that varied in angle and amount of added forces, the location of the added forces, and the activation time of the added forces, resulting in 231 simulation runs. We found that the most effective guidance technique was situation specific, because reducing or increasing the gymnast`s rotation speed and adding movement height are interdependent. To accompany a movement, it is possible to use an isolated hand application at the iliac crest during the flight phase of the salto, but for stronger support it is necessary to apply a guidance technique immediately at takeoff. When using a guidance technique that involves both hands, it seems that the timing of the hand application is more critical than the angle or amount of added force a coach uses.